PENERAPAN UNDANG-UNDANG TINDAK PIDANA KORUPSI OLEH JAKSA PENUNTUT UMUM PERKARA KASUS PENERBITAN SERTIFIKAT HAK MILIK DI KAWASAN HUTAN TAMAN NASIONAL TESO NILO - Khairunnas, Khairunnas (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
The study aimed to find out about the implementation of the Public Prosecution Corruption Act in the case of issuing property rights certificates in the Teso Nilo National Park Forest area and to find out the accountability for the issuance of certificates of ownership in the Teso Nilo National Park Forest area. This research was conducted using the normative legal analysis method. Based on the results of the study it was found that the application of the Corruption Crime Act by public prosecutors in the case of the issuance of ownership rights certificates in the Teso Nilo National Park HPT forest area was tried by a judge by justifying the actions taken by the defendant, but not a corruption but instead This is an administrative error whose authority is to try, namely the State Administrative Court (PTUN). This is of course unfair by not giving sanctions according to the defendant's reparations, and judges should be able to pay attention to the rights of the accused, as in progressive law law enforcement officers should be progressive or have breakthroughs so that the law is always active to give effect deterred according to the mistake made.